Model‐based reconstruction for real‐time phase‐contrast flow MRI: Improved spatiotemporal accuracy. Issue 3 (7th March 2016) - Tan, Zhengguo; Roeloffs, Volkert; Voit, Dirk; Joseph, Arun A.; Untenberger, Markus; Merboldt, K. Dietmar; Frahm, Jens
Abstract : Purpose: To develop a model‐based reconstruction technique for real‐time phase‐contrast flow MRI with improved spatiotemporal accuracy in comparison to methods using phase differences of two separately reconstructed images with differential flow encodings. Methods: The proposed method jointly computes a common image, a phase‐contrast map, and a set of coil sensitivities from every pair of flow‐compensated and flow‐encoded datasets obtained by highly undersampled radial FLASH. Real‐time acquisitions with five and seven radial spokes per image resulted in 25.6 and 35.7 ms measuring time per phase‐contrast map, respectively. The signal model for phase‐contrast flow MRI requires the solution of a nonlinear inverse problem, which is accomplished by an iteratively regularized Gauss‐Newton method. Aspects of regularization and scaling are discussed. The model‐based reconstruction was validated for a numerical and experimental flow phantom and applied to real‐time phase‐contrast MRI of the human aorta for 10 healthy subjects and 2 patients. Results: Under all conditions, and compared with a previously developed real‐time flow MRI method, the proposed method yields quantitatively accurate phase‐contrast maps (i.e., flow velocities) with improved spatial acuity, reduced phase noise and reduced streaking artifacts. Conclusion: This novel model‐based reconstruction technique may become a new tool for clinical flow MRI in real time. Magn Reson Med 77:1082–1093, 2017. © 2016 International Society for Magnetic Resonance in Medicine